Interface-based reduced coercivity and leakage currents of BiFeO3 thin films: A comparative study. (15th December 2018) - Tomczyk, Monika; Mahajan, Amit; Tkach, Alexander; Vilarinho, Paula M.
Abstract: Obtaining high quality BiFeO3 thin-films by low-cost scalable chemical solution deposition (CSD) is still challenging and currently relevant. Here we provide a comprehensive set of experimental evidences on the role of metallic (Pt) and oxide (IrO2 and LaNiO3 ) electrode interfaces on the texture development and functional properties improvement of CSD-derived BiFeO3 films. All BiFeO3 films are composed of columnar grains, which lateral size is dependent on the bottom electrode/interface. Whereas no texture was observed for 320 nm thick films fabricated on (111) oriented Pt, films on oxide electrodes, particularly on non-textured LaNiO3, are highly (012) oriented. Moreover, 400 nm thick BiFeO3 films on LaNiO3 possess a large remanent polarization 50 μC/cm 2, a small coercive field 150 kV/cm and a low leakage current density 4 × 10 −6 A/cm 2 at room temperature. In contrast, BiFeO3 films on the other electrodes reveal polarization hysteresis with high leakage current that increases with film thickness decrease. We demonstrate that LaNiO3 interfaces enhance crystallinity and orientation of BiFeO3 thin-films reflected in optimization of their functional properties. We advocate that besides the need of monophasic films, oxide electrodes and their interfaces have a relevant role on the development of high-quality BiFeO3 thin-films fabricated by CSD and derived devices. Graphical abstract: When comparing the electrical behaviour of IrO2, LNO and Pt based BiFeO3 thin films LNO is the most effective electrode in optimizing the electrical properties of films, templating film growth and enhancing their crystallinity and orientation. Hence BiFeO3 films on LNO possess a large remanent polarization of 50 μC/cm 2, a small coercive field of 150 kV/cm at room temperature and a low leakage current density 4 × 10–6 A/cm2. Highlights: The role of metallic (Pt) and oxide (IrO2 and LaNiO3 ) electrodes on the texture and functional properties of BiFeO3 films is disclosed. LaNiO3 is the most effective in optimizing the electrical properties of BiFeO3 films due to decreased stress, enhanced texture and crystallinity. BiFeO3 films are highly (012) oriented when deposited on non-textured oxide electrodes because of the natural growth habit of BiFeO3 along this plane. 400 nm thick BiFeO3 films on LaNiO3 possess a large Pr of 50 μC/cm 2, a small Ec of 150 kV/cm and a low J of 4 × 10 −6 A/cm 2 at room temperature.